Using temperature to trace river-groundwater interactions in alpine regions: A case study in the upper reaches of the Heihe River - Shuxun Zhang; Ziyong Sun; Yanxi Pan; Xin Li; Zhao Pan (Editorial Department of Bulletin of Geological Science and Technology, 2023)
Objective The alpine region is the source area of many large rivers globally, and understanding river-groundwater interactions in the region is critical to the scientific management of watershed water resources. Due to the widespread occurrence of permafrost, the distribution and dynamics of riverbed taliks play a vital role in controlling river-groundwater exchange in alpine regions, leading to the complex, unique characteristics of the hydraulic relationship between them. However, there have been few investigations on river-groundwater interactions in alpine regions due to the harsh field conditions, and these available studies have dominantly used isotope and hydrochemical tracing methods, which are expensive and not accurate. Methods In this study, the low-cost and accurate temperature signal was used as a tracer to quantify the exchange between river and groundwater. A vertical 1D transient heat transport analytical model was used to quantify river-groundwater exchange rates at different depths. The spatiotemporal variations in river-groundwater interactions were analyzed using the temperature data measured by a distributed optical fibre sensing system. Results Results show a substantial spatiotemporal variation in the exchange between river and groundwater in alpine regions. Season and climate can control the exchange rate between river and groundwater, and even the direction of exchange. It is also found that the exchange rate of river and groundwater increases with the depth of the active layer. Conclusion The study indicates that the temperature tracing method is suitable for studying river-groundwater interactions in alpine areas dominated by permafrost. Furthermore, the combination of two temperature tracing methods can effectively improve the accuracy and provide a feasible research framework for alpine regions where hydrogeological data are scarce.